Fear of AI and students’ psychological well-being through career anxiety - Sinta Nurul Oktaviana Kasim; Farida Aryani; Agus Qomaruzzaman (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2026)
The development of artificial intelligence (AI) presents opportunities and concerns for university students, particularly regarding changes in the world of work and emerging competency demands. This study analyzed the relationship between fear of AI and students’ psychological well-being through career anxiety. A quantitative correlational design was used. The participants were 428 university students obtained after data cleaning from 446 initial responses. The instruments measured fear of AI, career anxiety, and psychological well-being. Data were analyzed using descriptive statistics, Pearson correlation, regression, and mediation analysis with 5.000 bootstrap resamples. The results showed that fear of AI was positively associated with career anxiety (r = 0,386; p < 0,001), whereas career anxiety was negatively associated with psychological well-being (r = -0,352; p < 0,001). Career anxiety mediated the relationship between fear of AI and psychological well-being, with an indirect effect of -0,175 and 95% CI [-0,259, -0,101]. These findings highlight the importance of understanding fear of AI in students’ career development.